iGLAD 사고 분류 유형을 이용한 자전거 탑승자 교통사고 분석 - 이화수; 장은지; 임종현; 이지민; 김재훈; 송봉섭 (자동차안전학회지, 2018)
This paper reports an analysis of cyclist accident cases with respect to passenger vehicles on Korean roads. A typology based on Initiative for the Global Harmonization of Accident Data (iGLAD) code book is applied to a traffic accident analysis system(TAAS), which has the real-world crash data on Korea roads, to understand the accident scenarios in more detail and efficiently. Similarly this typology has been used for Germany In-Depth Accidents Study (GIDAS) as well. The accident data analysis with consideration of the typology of Korean road conditions may prioritize traffic safety issues regarding cyclists and is aimed to develop an Automatic Emergency Braking (AEB) system for cyclist. In summary, this paper characterizes and analyzes the scenarios of cyclist crashes with passenger car. The most common accident scenarios on Korean roads are Car-to-Bicyclist Nearside Adult (CBNA) and Car-to-Bicyclist Longitudinal Adult (CBLA), which are more than 86% of total accidents cases. Therefore, it is inferred that AEB cyclist system should include these accident types in the operational design domain to reduce more fatality in Korea.
Keywords: 능동안전; 충돌회피; 자동긴급제동; 자전거 탑승자; 교통사고 분석 시스템; Active Safety; Crash Avoidance; Autonomous Emergency Braking; Cyclist; Traffic Accident Analysis System